Motility induced changes in viscosity of suspensions of swimming microbes in extensional flows1. Issue 23 (21st June 2015) - McDonnell, Amarin G.; Gopesh, Tilvawala C.; Lo, Jennifer; O'Bryan, Moira; Yeo, Leslie Y.; Friend, James R.; Prabhakar, Ranganathan
<x xml:space="preserve">Abstract</x> Cell suspensions are model systems for studying properties of living materials. A comparison of theory against microfluidic experiments confirms that particle motility causes extensional viscosity to decrease in "pushers" and increase in "pushers".